2022
DOI: 10.1097/bsd.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Anterior Cervical Discectomy and Fusion Versus Posterior Percutaneous Endoscopic Cervical Keyhole Foraminotomy for Single-level Unilateral Cervical Radiculopathy

Abstract: Study Design: A systematic review and meta-analysis. Objective: The objective of this study was to compare the safety of microscopic anterior cervical discectomy and fusion (MI-ACDF) and posterior percutaneous endoscopic keyhole foraminotomy (PPEKF) in patients diagnosed with single-level unilateral cervical radiculopathy. Summary of Background Data: After conservative treatment, the symptoms will be relieved in about 90% of cervical radiculopathy patients. For the other one tenth of patients, surgical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…At five years, PCF cases had a significantly higher rate of subsequent cervical spine surgery relative to ACDF cases (19.0% vs. 14.8%). Prior literature had been mixed on this finding in the past, with some maintaining no difference between ACDF and PCF 10–12,25 while others found higher rates for PCF 13,14 . It is likely that greater statistical power afforded by greater patient numbers in the current study was needed to identify this difference.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…At five years, PCF cases had a significantly higher rate of subsequent cervical spine surgery relative to ACDF cases (19.0% vs. 14.8%). Prior literature had been mixed on this finding in the past, with some maintaining no difference between ACDF and PCF 10–12,25 while others found higher rates for PCF 13,14 . It is likely that greater statistical power afforded by greater patient numbers in the current study was needed to identify this difference.…”
Section: Discussionmentioning
confidence: 82%
“…12 A meta-analysis by Guo et al, found no significant differences in pooled total complication rates and revision rates between single-level ACDF and PCF groups. 13 Another meta-analysis from Fang et al found perioperative outcomes to be similar between the groups, but unlike the previous review, significantly higher revision rates for those undergoing PCF. 14 Given the mixed literature regarding outcomes of ACDF versus PCF, establishing the relative risks and benefits of both approaches is critical for guiding proper surgical decision-making.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Regardless of the cervical anterior or posterior approach method, several literatures on the complications of full endoscopic cervical surgery have already been reported. According to the analysis of complications of endoscopic spinal surgery, Guo et al 41 reported total complication rate of 4.7% and a reoperation rate of 1.1% in cervical endoscopic surgery. In anterior full en-doscopic cervical surgery, recurrent laryngeal nerve injury and swallowing dysfunction are unique complications of this method.…”
Section: Complications Of Endoscopic Cervical Spinal Surgerymentioning
confidence: 99%